1999
DOI: 10.1542/peds.103.4.748
|View full text |Cite
|
Sign up to set email alerts
|

Ipratropium Bromide Added to Asthma Treatment in the Pediatric Emergency Department

Abstract: The addition of three doses of ipratropium to an ED treatment protocol for acute asthma was associated with reductions in duration and amount of treatment before discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(32 citation statements)
references
References 16 publications
0
29
0
3
Order By: Relevance
“…It was expected that LOS data would be skewed, so a sample size calculation was made with a non-parametric adjustment allowing for unequal variances in both LEV and RAC/IB groups. Assuming standard deviations of 50 and 60 min, and a two-sided alpha error rate of 5%, 70 subjects per treatment group (140 subjects total) provided 80% power to detect a 25 minute difference in ED LOS (4).…”
Section: Discussionmentioning
confidence: 99%
“…It was expected that LOS data would be skewed, so a sample size calculation was made with a non-parametric adjustment allowing for unequal variances in both LEV and RAC/IB groups. Assuming standard deviations of 50 and 60 min, and a two-sided alpha error rate of 5%, 70 subjects per treatment group (140 subjects total) provided 80% power to detect a 25 minute difference in ED LOS (4).…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, effective when added to a SABA in the context of severe exacerbations [4••, [51][52][53]. Treatment with inhaled ipratropium combined with albuterol in the emergency room reduced hospital admissions and improved lung function, particularly in patients with FEV 1 <30 %, and symptoms for more than 1 day [54,55]. Although other studies have concluded that did not reduce the length of hospitalization or admission to intensive care unit [56], a Cochrane Review concluded that nebulized ipratropium combination with a SABA significantly reduces the risk of hospital admission and other had other clinically important outcomes [57].…”
Section: And Severe Exacerbationsmentioning
confidence: 99%
“…to inicial da criança 2 inclui a utilização de beta-2-agonistas, agentes anticolinérgicos (brometo de ipratrópio) [3][4][5][6][7][8] , administrados em conjunto com os beta-2-agonistas e corticói-des por via sistêmica 9. Entretanto, o papel de outras drogas no tratamento inicial da asma aguda ainda não está totalmente esclarecido.…”
Section: Veja Artigo Relacionado Na Página 279unclassified